ASSESSMENT OF ASPROSIN, TROPONIN, AND OTHER VARIABLES IN CARDIOVASCULAR DISEASES - Suzan K. Mohammed, Nihad N. Hilal (South Eastern European Journal of Public Health, 2025)
Background: Asprosin is a newly discovered hormone produced during fasting and promotes the liver to release glucose into the bloodstream. Aim of the study: Evaluating the Troponin, asprosin, lipid profile, and liver function test in the blood serum of cardiovascular patients to find predictive significance of diagnosis for this disease. Methods: In this study, 140 samples have been collected (70 patients with cardiovascular disease, and 70 control) and distributed among different ages (40-60years) and for both genders from patients in Cardiac Care Unite (CCU) in Kirkuk Teaching Hospital and Azadi Teaching Hospital in Kirkuk city, from (27/11/2023) to (28/2/2024). The control groups consist of 70 subjects. They were collected from medical staff and relatives who were free from signs and symptoms of cardiovascular disease. Results: The present study showed increased level of Asprosine, Troponin, cholesterol, Triglycerides, LDL, VLDL, AST and ALT in patients with CVD that were (3.36±1.50 ng/ml, 97.7±32.6 ng/ml, 225.1±25.2 mg/dl, 209.5±8.3 mg/dl, 140.7±17.9 mg/dl, 41.9±4.61 mg/dl, 54.32±22.1 U/L, 44.18±7.17 U/L) compared with the control group that were (1.68± 0.15 ng/ml, 69.37± 13.69 ng/ml, 196.3±27.2 mg/dl, 165±6.1 mg/dl, 113.67±15.2 mg/dl, 33.00±3.22 mg/dl, 29.54±6.57 U/L, 21.33±5.43 U/L)respectively. A significant decrease in HDL in CVD patients was(42.5±7.97 mg/dl) as compared with the control which was(49.33±6.38 mg/dl)respectively. Conclusion: This study concluded an increase in aspronin and troponin in patients with CVD. In addition dyslipidemia and an increase in both AST and ALT in CVD patients.